Pengaruh Pelatihan dan Karakteristik Individu Terhadap Kinerja KaryawanDi PT. Multi Bintang Indonesia Tbk Sampangagung Kutorejo Mojokerto - Dian Mafulla (El-Idaarah, 2021)
The aim of this research is to analyze the effect of training and individual characteristics on employee performanceat PT. Multi Bintang Indonesia Tbk Sampangagung Kutorejo Mojokerto. This study uses correlational quantitativeresearch methods. Determination of the sample in this study was taken 50% of the population using ProportionalRandom Sampling, namely as many as 54 respondents. The data was collected using a questionnaire that had beentested for validity and reliability. The data analysis used is multiple linear regression analysis with the help of theSPSS 16.0 For Windows program. Based on the results of the analysis it can be concluded that: there is a significantpositive effect of training and individual characteristics partially on employee performance at PT. Multi BintangIndonesia Tbk Sampangagung Kutorejo Mojokerto, this is evidenced by the t count value of training (2,103)> t table(2,010) and the value of individual characteristics t count (8,829)> t table (2,010). There is a significant positive effectof training and individual characteristics simultaneously on employee performance at PT. Multi Bintang IndonesiaTbk Sampangagung Kutorejo Mojokerto, this is evidenced by the value of Fcount (38,382)> Ftable (4,04). That thedominant individual characteristics affect the performance of employees at PT. Multi Bintang Indonesia TbkSampangagung Kutorejo Mojokerto, this is evidenced by the tcount of individual characteristics (8,829)> the tcount oftraining (2,103).